2015
DOI: 10.1038/srep17747
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear, non-monotonic effect of nano-scale roughness on particle deposition in absence of an energy barrier: Experiments and modeling

Abstract: Deposition of colloidal- and nano-scale particles on surfaces is critical to numerous natural and engineered environmental, health, and industrial applications ranging from drinking water treatment to semi-conductor manufacturing. Nano-scale surface roughness-induced hydrodynamic impacts on particle deposition were evaluated in the absence of an energy barrier to deposition in a parallel plate system. A non-linear, non-monotonic relationship between deposition surface roughness and particle deposition flux was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 58 publications
5
45
0
Order By: Relevance
“…Theoretically, the number of adhered cells per area ( ⁄ ) is directly related to the cell flux (equation 7) and, consequently, to the experimental Sherwood number [39]:…”
Section: Boundary Conditions and Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the number of adhered cells per area ( ⁄ ) is directly related to the cell flux (equation 7) and, consequently, to the experimental Sherwood number [39]:…”
Section: Boundary Conditions and Numerical Proceduresmentioning
confidence: 99%
“…A uniform concentration of 0.35 kg•m -3was considered at the antechamber inlet and at the bottom walls, the cell concentration was set to zero since it is assumed that all the cells that arrive at the wall stay instantaneously immobilized and therefore disappear from the dispersed phase. This is the so-called perfect sink model, and it is the most commonly used boundary condition at the collectors surface[24,39,40]. In these wall conditions (i.e.…”
mentioning
confidence: 99%
“…In addition, surface roughness played an important role in particle deposition experiment/ simulation. They conducted another study on deposition of colloidal particles and reported a non-monotonic, non-linear effect of nanoscale roughness on particle deposition without energy barrier using both the convection-diffusion model and parallel-plate chamber experimental system [102]. Their results showed particle deposition flux could reach the minimum value when a critical roughness size was provided.…”
Section: Theoretical Modelling/studiesmentioning
confidence: 99%
“…32,33 Biological filtration processes range from classical-biofiltration in an otherwise conventional treatment plant (i.e., preceded by coagula-tion/flocculation/clarification and sometimes advanced oxidation processes such as pre-ozonation)-to slow sand filtration (SSF) that is typically operated without chemical or other types of pre-treatments. 28,32 Thus, while they may include physico-chemical filtration that relies on synergies between particle size, media depth, media size, particle destabilization by coagulation, and media roughness, [35][36][37][38] biodegradation, biotransformation, adsorption, and bioregeneration may also contribute to treatment. Critically, however, biological filtration performance is not directly proportional to the amount of biomass present; 31,39,40 thus, lab-and pilot-scale assessments remain critical to demonstrating biological treatment capabilities.…”
Section: Introductionmentioning
confidence: 99%